2017
DOI: 10.1007/s00359-017-1167-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic activation in the brain of the migratory northern wheatear (Oenanthe oenanthe)

Abstract: Behavioural and neurobiological evidence suggests the involvement of the visual and trigeminal sensory systems in avian magnetoreception. The constantly growing array of new genetic approaches becoming available to scientists would bear great potential to contribute to a generally accepted understanding of the mechanisms underlying this ability, but would require to breed migratory birds in captivity. Here we show that the transcontinental night-migratory Northern Wheatear (Oenanthe oenanthe), which is current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 62 publications
4
46
0
Order By: Relevance
“…Anaesthesia with lidocaine applied to the mucous skin of the upper beak, as has been used in numerous studies in order to temporarily 'inactivate' a beak-based magnetic sensor, did not significantly affect the magnetic activation of trigemino-recipient brain structures PrV and SpV in migratory European robins, whereas sectioning of V1 led to a significant decrease in magnetic field-induced neuronal activation (figure 1g). Previous studies replicably showed that the observed activation is mediated by V1 and that it is very likely to be induced by magnetic stimuli, because downregulation of Egr-1 was achieved both by V1 sectioning and by compensation of the ambient magnetic field [51][52][53].…”
Section: General Observationsmentioning
confidence: 59%
See 3 more Smart Citations
“…Anaesthesia with lidocaine applied to the mucous skin of the upper beak, as has been used in numerous studies in order to temporarily 'inactivate' a beak-based magnetic sensor, did not significantly affect the magnetic activation of trigemino-recipient brain structures PrV and SpV in migratory European robins, whereas sectioning of V1 led to a significant decrease in magnetic field-induced neuronal activation (figure 1g). Previous studies replicably showed that the observed activation is mediated by V1 and that it is very likely to be induced by magnetic stimuli, because downregulation of Egr-1 was achieved both by V1 sectioning and by compensation of the ambient magnetic field [51][52][53].…”
Section: General Observationsmentioning
confidence: 59%
“…Finally, it was shown that V1 sectioning had no unspecific effects on the birds' ability to show migratory behaviour and to use their magnetic compass, because V1-lesioned birds oriented as well as controls in magnetic compass orientation experiments [8,24,54,55]. Based on the above considerations, we have repeatedly argued that V1 sectioning is the only sure way to prevent trigeminal magnetic information being transmitted to the brain via V1 [9,10,24,52,53,55,56].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In many regions of the world, total intensity and inclination (the angle between the magnetic field lines and the horizon) of the geomagnetic field varies approximately along a north-south axis, whereas declination (the angle between directions towards the magnetic and geographic poles) changes primarily along an east-west axis (Boström et al 2012; https ://ngdc.noaa.gov/ geoma g/WMM/image .shtml ). The trigeminal nerve has been shown to be involved in the avian magnetoreception (Heyers et al 2010;Lefeldt et al 2014;Elbers et al 2017), but it is not required for magnetic compass orientation (Zapka et al 2009). A further displacement experiment from the Courish Spit to Moscow demonstrated that an intact trigeminal nerve is necessary for the compensatory response shown by Reed Warblers (Kishkinev et al 2013).…”
Section: Introductionmentioning
confidence: 99%